2014
DOI: 10.3109/02713683.2014.884598
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Interleukin-1β-Induced Matrix Metalloproteinase Expression in Human Corneal Fibroblasts by Tranilast

Abstract: Tranilast inhibits the IL-1β-induced production of MMP-1, -2, and -3 by human corneal fibroblasts, with this action likely being mediated through suppression of MAPK and NF-κB signaling pathways. Tranilast thus warrants further investigation as a potential treatment for corneal ulceration on the basis of its inhibition of MMP expression in corneal fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“… 24 Moreover, a previous study found that IL-1β stimulated the expression of MMP2 and MMP9. 25 VCAM-1 is an inflammatory mediator secreted from endothelial cells and has been identified as a marker of endothelial dysfunction in the inflammatory response, 26 whereas endothelial injury and dysfunction are compulsory conditions for the development of thrombosis. 27 In addition, IL-1β increases the expression of VCAM-1 to improve cardiac function following an ischemic attack.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Moreover, a previous study found that IL-1β stimulated the expression of MMP2 and MMP9. 25 VCAM-1 is an inflammatory mediator secreted from endothelial cells and has been identified as a marker of endothelial dysfunction in the inflammatory response, 26 whereas endothelial injury and dysfunction are compulsory conditions for the development of thrombosis. 27 In addition, IL-1β increases the expression of VCAM-1 to improve cardiac function following an ischemic attack.…”
Section: Discussionmentioning
confidence: 99%
“…PPAR-α activation has been also reported to cause neuroprotection in neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, and multiple sclerosis (MS) [ 93 , 94 ]. In another study, Tranilast had inhibited the production of MMP-1, 2, 3 induced by IL-1 in human corneal fibroblasts by the inhibition of some signaling pathways such as mitogen-activated protein kinase (MAPK) and NF-κB, as the main pathways for inflammatory responses [ 95 ]. This drug had appeared to inhibit MCP-1 production by impairing NF-κB and c-Jun N-terminal kinase (JNK) signaling pathways [ 81 ].…”
Section: A Body Of Literaturementioning
confidence: 99%
“…Several studies have confirmed that IL-1␤ had the function of stimulating the production of MMPs in corneal fibroblasts (37,49), and, taking into account our previous studies, senescent corneal fibroblasts promoted CNV by enhancing the expression of MMPs and other genes related to the generation of neovascularization (53). Therefore, we compared the different expression levels of angiogenesis-related genes in normal or senescent fibroblasts pretreated with or without IL-1␤.…”
Section: C739mentioning
confidence: 72%
“…As a major secretory factor in SASP, IL-1␤ reportedly plays an important physiological role in the tissue microenvironment regulated by senescent cells. Moreover, IL-1␤ has already been confirmed to induce the upregulation of MMP expression in cornea (15,26,37,45,49).…”
Section: Introductionmentioning
confidence: 89%